Endogenous asymmetric money illusion - Duarte, Diogo; Saporito, Yuri F. (Journal of Banking & Finance, 2019)
We show that when investors suffer from endogenous asymmetric money illusion, the usual proportionality between money supply and nominal prices commonly present in frictionless economies is eliminated. This drives changes in the money supply to cause real price fluctuations. Nevertheless, the combined effect on the real state price density and the price of money leads the nominal state price density, and consequently nominal bond prices, to be independent of money illusion. This article thus provides a theoretical foundation for Modigliani-Cohn’s conjecture that money illusion impacts stock markets but not bond markets.